Pelatihan Risalah Kewanitaan terhadap Para Wanita di Desa Bluri Solokuro Lamongan - Aminah, Siti; Musthofa, R. Zainul; Finurika, Isyna (Keris: Journal of Community Engagement, 2024)
This service is expected to help improve public understanding in the religious and social fields, especially for residents of Bluri Village, Solokuro District, Lamongan Regency. To improve the understanding of women's treatises for women in Bluri Village, student researchers conducted seminars and training activities with direct material presentation methods, including explanations of menstruation, postpartum, and istihadloh related to the differences and similarities, how to distinguish menstruation and istihadloh, and how to calculate menstruation and istihadloh which can be practiced directly by the community. Community service activities in the form of seminars and training on women's treatises were held on Monday, August 21, 2024 at the Ihyaul Ulum diniah locality which was held at 20.00 - 23.00 WIB. Training activities include delivering material explaining the work program, the background of women's problems, introduction to menstruation, and istihadloh, how to calculate days and limits, how to purify, and the worship of istihadloh people. continued with a question and answer session and group photos. Based on the results of the socialization and training conducted, the community was enthusiastic in the process of the seminar and training of this women's treatise. In this case, the service was focused on Mrs. Fatayat and IPPNU because most mothers and young women in this village did not know about it.